Learning from our vulnerabilities: Insights from Octavia E. Butler’s parable of the sower and West Sumatra’s 2024 flood disasters - Sandika Edria; Rizano Gindho; Yeni Marliza (E3S Web of Conferences)
This article discusses the correlation between flood disasters in West Sumatra in March and May 2024 and the science fiction novel Parable in the Sower by Octavia E. Butler. The novel explores how social and environmental degradation amidst the extreme weather and climate change in the fictional setting of America in 2024-2027 mirrors West Sumatra’s lack of preparedness to face similar situations in reality. The novel warns people of the consequences of environmental issues by addressing our vulnerabilities and resistance to change. Through the concept of “Earthseed”, the story reminds society to work toward positive changes through resilient infrastructure, disaster preparedness, and empathy when facing natural disasters.